Integrating Local Ecological Knowledge for Waterbird Conservation: Insights From Kavango-Zambezi Transfrontier Conservation Area, Zimbabwe. (September 2018) - Tarakini, Tawanda; Guerbois, Chloé; Wencelius, Jean; Mundy, Peter; Fritz, Hervé
Weaving local and scientific knowledge systems is important to enhance understanding, practice, and ethics toward natural resources sustainable utilization. We focused on wetlands and waterbirds and used local knowledge and perceptions by key informants in and around a protected area in Zimbabwe to investigate (a) trends in rainfall and water quality, (b) waterbird trends and associated uses, and (c) drivers, mechanisms, and impacts behind waterbird trends, to understand waterbird ecological dynamics. We confronted these perceptions to available data locally and globally. Furthermore, we explored local ideas to improve waterbird survival. Associations between informant variables and trends in water quality were tested using the χ 2 test while multiple correspondence analyses were used to explore drivers, mechanisms, and impacts of bird trends. Wildfowl were cited the most (48.7% of all citations), probably linked to their use as food, and they were negatively driven by human predation but would increase when left to follow natural processes. Changes in natural processes and wetlands drove large piscivores into decline, but their populations would increase when predation was controlled. Generalist species responded positively when climate and resources were not limiting. We then discus the feasibility of the suggested waterbird conservation remedies: education, increasing surface water, law enforcement, sustainable use guidelines, and modified drinking troughs for large herbivores. Local knowledge and available local trends data were inconsistent with International Union for the Conservation of Nature trend status. The local sources of knowledge were not correlated but broadly consistent. We also discuss the scale discrepancies and how the sources of information can be complementary.